DETERMINAN AUDITOR SWITCHING (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2015-2016) - Fitri Romadhoni, 14.05.52.0103; Jaeni, Jaeni (Students' Journal of Accounting and Banking, 2018)
The purpose of this research was to determine the effect size of the Public Accounting Firm (KAP), the size, growth of client companies, financial distress, turnover manajamen audit opinion, tenure audite to the auditor switching. This research uses explanatory study, the research describes the relationship between variables. The type or types of relationships in this study is a causal link between one or more variables. Samples were taken by using purposive sampling technique. Samples were 60 companies from 120 companies listed in Indonesia Stock Exchange in 2015-2016, so that the research data was analyzed totaled 60. To analyze the hypothesis used logistic regresion analysis. The results indicate that firm size, growing of client company, financial distress, Change of management, audit opinion and tenure audit not showed effect on auditor switching. Size of client showed negative and significant effect on auditor switching.Key words: Auditor switching, Firm size, Size of client, Growth of client company, Financial distress, Change of management, Audit opinion and Audit Tenure